The Use of Typomorphic Features of Native Gold for the Solution of Geological Exploration - Guseinov, G.S.; Mammedov, I.A. (Herald of Azerbaijan Engineering Academy, 2022)
The article examines the typomorphic features of native gold in different types of ores of the described region, which make it possible to address issues directly related to the practice of geological exploration. So, the established elements-impurities included in the composition of gold make it possible to use it as additional information when specifying the conditions for the formation of deposits, and the identification of the internal structure allows the depth of deposition, the stages of ore formation. The complex use of typomorphic features of native gold makes it possible to evaluate the processing of ores, which is of great practical importance in the industrial development of deposits.